Darwin and Deep Time: Temporal Scales and the Naturalist's Imagination. (March 2016) - Dear, Peter
Charles Darwin built a world around an implied metaphysics of time that treated deep time as something qualitatively different from ordinary, experienced time. He did not simply require a vast amount of time within which his primary evolutionary mechanism of natural selection could operate; in practice, he required a deep time that functioned according to different rules from those of ordinary, "shallow" time. The experience of the naturalist occupied shallow time, but it was from that experience that Darwin necessarily had to build his arguments concerning a transformism that took place on an entirely different temporal scale. Much of his reconstruction of what took place in deep time relied on inferences drawn from taxonomic classification, and those inferences in turn depended to a large degree on conclusions reached through the already-established practices of his fellow non-transformist naturalists. By bootstrapping his transformist arguments, focused on both natural and sexual selection, with non-transformist classificatory judgments, Darwin attempted to convince his fellow naturalists of the truth of evolution in deep time. In other words, while Darwin argued for the existence of selectionist processes themselves in contemporary shallow time, their transformist consequences could only be traced out in deep time, being evidenced by both contemporary and paleontological slices, or laminae, of shallow time. This served to protect transformism from the dangers of unorthodoxy by preserving uniformity within shallow time.